2017
DOI: 10.1038/ncomms15539
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis identifies five novel loci associated with endometriosis highlighting key genes involved in hormone metabolism

Abstract: Endometriosis is a heritable hormone-dependent gynecological disorder, associated with severe pelvic pain and reduced fertility; however, its molecular mechanisms remain largely unknown. Here we perform a meta-analysis of 11 genome-wide association case-control data sets, totalling 17,045 endometriosis cases and 191,596 controls. In addition to replicating previously reported loci, we identify five novel loci significantly associated with endometriosis risk (P<5 × 10−8), implicating genes involved in sex stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
317
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 261 publications
(340 citation statements)
references
References 70 publications
9
317
0
14
Order By: Relevance
“…It is important to distinguish whether these overlaps are coincident or true shared causal variants. We used summary data-based Mendelian randomization (SMR) analysis (41,47) to test for association between RANKL expression and BMD GWAS signals at six eQTL SNPs. The SMR identified RANKL as the causal gene underlying BMD GWAS association (p < 5 Â 10 -5 ), and there was no significant heterogeneity underlying the eQTL signals (p HEIDI > 0.05) (Supporting Table 5), suggesting that the same causal SNPs contributed to both osteoporosis risk and RANKL expression at 13q14.11.…”
Section: Cis-eqtl Analyses Identified Six Regulatory Snps At 13q1411mentioning
confidence: 99%
“…It is important to distinguish whether these overlaps are coincident or true shared causal variants. We used summary data-based Mendelian randomization (SMR) analysis (41,47) to test for association between RANKL expression and BMD GWAS signals at six eQTL SNPs. The SMR identified RANKL as the causal gene underlying BMD GWAS association (p < 5 Â 10 -5 ), and there was no significant heterogeneity underlying the eQTL signals (p HEIDI > 0.05) (Supporting Table 5), suggesting that the same causal SNPs contributed to both osteoporosis risk and RANKL expression at 13q14.11.…”
Section: Cis-eqtl Analyses Identified Six Regulatory Snps At 13q1411mentioning
confidence: 99%
“…Causes of endometriosis remain largely unknown, but the condition has an estimated heritability of ∼ 50% [3, 4] with ∼26% estimated to be due to common genetic variation [5]. In total eight genome-wide association studies (GWAS) in women of European and East Asian ancestry have been published to date [6], the largest of which comprised 17,045 cases and 191,596 controls and identified 19 distinct signals at 14 loci [7], leaving many loci yet to be uncovered. Although positional evidence had suggested potential involvement of sex-steroid hormone, WNT signalling, cell adhesion/migration, cell growth/carcinogenesis and inflammation-related pathways, the regulatory effects of most of these variants have yet to be determined in tissues relevant to endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Women with endometriosis have a lower monthly fecundity rate than fertile controls [3]. A meta-analysis of 22 published studies showed that women with endometriosis undergoing in vitro fertilization (IVF) had significantly reduced oocyte retrieval, fertilization, and implantation rates, as well as a significantly lower chance of achieving pregnancy, compared to patients with tubal factor [4].…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is a complex trait, with both genetic and environmental factors contributing to the pathophysiology of the disease. The heritability of endometriosis is estimated to be 47-51% [14,15], but the 13 loci identified by previous genome-wide association studies (GWASs) only explain 1.75% of the phenotypic variance [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%